Krisis identitas lembaga pendidikan Islam di Era digital: Antara tradisi dan modernisasi - Nur Aini; Eka Alzahra; Herlini Puspika Sari (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2026)
The development of digital technology has brought significant changes to various aspects of life, including the Islamic education system. These changes have created new challenges for Islamic educational institutions in maintaining a balance between the traditional values that characterize Islamic education and the demands of modernization and digitization of education. This article aims to analyze the phenomenon of identity crisis in Islamic educational institutions in the digital era and examine various strategies that can be implemented to maintain the identity of Islamic education amid technological developments. This study uses a qualitative approach with library research, namely by analyzing various scientific literature such as books, journals, and research results relevant to the topic of study. The results show that the identity crisis of Islamic educational institutions arises from the tension between efforts to maintain the traditional values of Islamic education and the demands of modernization of education based on digital technology. In addition, digitization also brings various challenges such as low digital literacy, limited human resources, and the potential for a shift in moral and spiritual values in the educational process. Therefore, Islamic educational institutions need to develop integrative strategies through strengthening the Islamic values-based curriculum, improving teacher competence in teaching, and enhancing the role of religious leaders in shaping the educational process.